Degradation of PVDF-based composite membrane and its impacts on membrane intrinsic and separation properties - Lee, Mei Jiun (Walter de Gruyter GmbH, 2016)
In this work, an attempt was made to evaluate the effects of ultraviolet (UV) irradiation period on the intrinsic and separation properties of composite membrane composed of organic polyvinylidene fluoride and inorganic titanium dioxide (TiO2) nanoparticles by exposing the membrane to UV-A light for up to 250 h. The changes on membrane structural morphologies and chemical characteristics upon UV exposure were studied by field-emission scanning electron microscope and Fourier transform infrared, respectively. It was observed that some cracks and fractures were formed on the membrane outer surface when it was exposed to 120-h UV light. Further increase in UV irradiation time to 250 h had caused membrane structure to collapse, turning it into powder form. Filtration experiments showed that the permeate flux of irradiated membrane was significantly increased from 10.89 L/m2 h to 21.84 L/m2 h (>100% flux increment) while oil rejection decreased with increasing UV exposure time from 0 h to 120 h. Furthermore, the mechanical strength and thermal stability of irradiated membrane were also reported to decrease with increasing UV exposure time, suggesting the negative impacts of UV light on the membrane overall stability. This research is of particular importance to evaluate the suitability and sustainability of polymeric membrane, which is widely considered as the host for photocatalyts and used for wastewater treatment process under UV irradiation.